2001
DOI: 10.1017/s0048577201990559
|View full text |Cite
|
Sign up to set email alerts
|

On the utility of P3 amplitude as a measure of processing capacity

Abstract: The present review focuses on the utility of the amplitude of P3 of as a measure of processing capacity and mental workload. The paper starts with a brief outline of the conceptual framework underlying the relationship between P3 amplitude and task demands, and the cognitive task manipulations that determine demands on capacity. P3 amplitude results are then discussed on the basis of an extensive review of the relevant literature. It is concluded that although it has often been assumed that P3 amplitude depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

129
1,198
17
16

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,533 publications
(1,360 citation statements)
references
References 162 publications
(240 reference statements)
129
1,198
17
16
Order By: Relevance
“…The lack of significant differences in ERP on the Go/NoGo task between SUD treatment completion groups may suggest that the Go/NoGo task is sufficiently complex to require participants in both groups to devote attentional resources during participation. Task demands have been shown to alter P300 responses related to context‐updating theory (Polich 2007); specifically, the more demanding the cognitive task, the smaller the P300 amplitude (Polich 1987; Kok 2001). The implication of these findings is that the participants who discontinued treatment early may have missed the sometimes subtleties that exist in therapy, the relevance to their own lives, and the benefits of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of significant differences in ERP on the Go/NoGo task between SUD treatment completion groups may suggest that the Go/NoGo task is sufficiently complex to require participants in both groups to devote attentional resources during participation. Task demands have been shown to alter P300 responses related to context‐updating theory (Polich 2007); specifically, the more demanding the cognitive task, the smaller the P300 amplitude (Polich 1987; Kok 2001). The implication of these findings is that the participants who discontinued treatment early may have missed the sometimes subtleties that exist in therapy, the relevance to their own lives, and the benefits of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, a larger P3 amplitude is assumed to reflect the employment of increased attentional resources (Kok, 2001). However, as it was shown, P3 would also indicate the amount of resources available for stimulus processing, therefore an amplitude reduction and latency increase suggested that resources were needed elsewhere (Beauducel et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Tasks that are highly demanding require a great amount of energy to perform successfully, in which case the individual is not likely to be in the appropriate energetic state. The individual must then increase effort to mobilise energetic resources in order to equilibrate their energetic state with the energetic requirements of the task (Kok, 2001;Robert and Hockey, 1997). According to the CEM, in situations of sub-optimal energetic state, individuals with AD/HD cannot successfully adjust their energetic state to the level required by the task.…”
Section: Introductionmentioning
confidence: 99%
“…A parietally maximal P3 component has been identified in a variety of paradigms whose latency has been associated with the time taken to evaluate a stimulus (Polich and Kok, 1995) and amplitude related to the amount of information transferred to working memory (Kok, 2001;Polich and Kok, 1995;Wiersema et al, 2006a). In the flanker task this component is maximal centro-parietally, and is enhanced and delayed to incongruent stimuli compared to other stimulus types in both adults (Folstein and Van Petten, 2008;Ridderinkhof and van der Molen, 1995) and children Rueda et al, 2004).…”
Section: Introductionmentioning
confidence: 99%